Pendampingan BLUD Kesehatan dalam Penyusunan Posisi Keuangan di Kabupaten Musi Banyuasin - Nilam Kesuma; Aspahani; Eka Meirawati; Asfeni Nurullah (Sriwijaya Accounting Community Services, 2022)
One of the UPTD Regional Apparatus Work Units that can be transformed into a BLUD is the Puskesma. The UPT of the Health Service in Musi Banyuasin Regency (MUBA) has not yet implemented the Financial Management Pattern of the Regional Public Service Agency (PPK-BLUD), so its service performance is not optimal and inflexible in meeting community satisfaction. The target audience chosen are the managers and treasurers of the puskesmas who are heading to become PPK of the BLUD Puskesmas in Musi Banyuasin Regency as many as 39 people. The implementation of this service activity is carried out within a period of 2 months starting from a survey, providing training for 2 days and continuing with direct assistance. The implementation of this Community Service activity is carried out using the lecture, tutorial, and discussion methods. The systematic implementation of this service activity is carried out in a blended manner, which is partly offline and partly online. Based on the evaluation designed to assess the success of the implementation of this service, it was seen that there was an increase in participants' knowledge. Limited resources are owned because not all BLUD officials who prepare financial statements have an accounting education background.